2020
DOI: 10.1002/ana.25861
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis: Fuel for the Corticofugal Feud

Abstract: This commentary provides perspective on the report by Burg et al that corticospinal motor neurons provoke corticofugal spread of motor neuron degeneration in amyotrophic lateral sclerosis (ALS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Recent studies also confirmed the importance and relevance of UMNs in ALS pathology. When UMNs were ablated from the SOD1 mouse models by crossing with the fezf2 null, the results revealed that UMNs indeed play an important role for initiating and modulating disease pathology and that their degeneration is not by mere consequence 72,105 . In addition, floxed hSOD1 G37R mice recapitulate UMN loss.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies also confirmed the importance and relevance of UMNs in ALS pathology. When UMNs were ablated from the SOD1 mouse models by crossing with the fezf2 null, the results revealed that UMNs indeed play an important role for initiating and modulating disease pathology and that their degeneration is not by mere consequence 72,105 . In addition, floxed hSOD1 G37R mice recapitulate UMN loss.…”
Section: Discussionmentioning
confidence: 97%
“…When UMNs were ablated from the SOD1 mouse models by crossing with the fezf2 null, the results revealed that UMNs indeed play an important role for initiating and modulating disease pathology and that their degeneration is not by mere consequence. 72,105 In addition, floxed hSOD1 G37R mice recapitulate UMN loss. When mutant hSOD1 G37R is removed from UMN of floxed mice by crossing them with the CrymCreER T2 mice, UMN loss is prevented suggesting that UMN degeneration relies on cell autonomous mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In motor neuron diseases, such as hereditary spastic paraplegia (HSP), primary lateral sclerosis (PLS) and amyotrophic lateral sclerosis (ALS), this complex circuitry degenerates [ 4 13 ]. There has been a long debate in the field about relevant contribution of different components of the circuitry so that targeted therapies can be developed [ 14 21 ]. Many argued that corticospinal motor neuron (CSMN) or the upper motor neuron (UMN) degeneration is a byproduct or a consequence of the “die-back” phenomenon [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%